1995
DOI: 10.1159/000246487
|View full text |Cite
|
Sign up to set email alerts
|

IgA Deficiency and Psoriasis: Relevance of IgA in the Pathogenesis of Psoriasis

Abstract: A psoriatic patient with absolute deficiency of IgA is reported. The manifestations of poriasis appeared at the age of 6 months and proved to be resistant to various treatments. The present case report and the data available in the literature on IgA and psoriasis all converge on the hypothesis that IgA is a systemic factor which belongs to the ‘off switches’ of the psoriatic process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Aetiopathogenesis of this dermatosis is complex and not yet well known. In recent years, attention has been paid to probability of primary intestinal absorption disorders in psoriatics 1 and to IgA protective role 2 . It has also been observed that psoriasis can coexist with clinically asymptomatic celiac disease and a gluten‐free diet helps to obtain remission, even in patients with very chronic lesions 3–5 .…”
Section: Introductionmentioning
confidence: 99%
“…Aetiopathogenesis of this dermatosis is complex and not yet well known. In recent years, attention has been paid to probability of primary intestinal absorption disorders in psoriatics 1 and to IgA protective role 2 . It has also been observed that psoriasis can coexist with clinically asymptomatic celiac disease and a gluten‐free diet helps to obtain remission, even in patients with very chronic lesions 3–5 .…”
Section: Introductionmentioning
confidence: 99%
“…In the present study the only girl with IgA deficiency had psoriasis. This might be a coincidence, but such a combination has previously been reported, and it is possible that IgA deficiency predisposes to the development of this disorder [26]. …”
Section: Discussionmentioning
confidence: 96%
“…Both systemic and organ-specific AD have been reported in IgAD, including autoimmune hemolytic anemia and idiopathic thrombocytopenic purpura (Cunningham-Rundles, 2002), dermatomyositis (Claman et al, 1970), Henoch-Schonlein purpura (Martini et al, 1985), pernicious anemia (Spector, 1974;Kätkä et al, 1988), psoriasis (van de Kerkhof and Steijlen, 1995), primary biliary cirrhosis (James et al, 1986), and vitiligo (Torrelo et al, 1992). Associations of IgAD with common systemic AD are summarized in Table 1.…”
Section: Autoimmunitymentioning
confidence: 99%